Response of Soil Microarthropod Community to Seasonal Changes in Urat Desert Steppe, Inner Mongolia - Guo, Zhixia; Chang, Haitao; Liu, Rentao (Frontiers in Environmental Science, 2022)
The abiotic factors viz., moisture and temperature play the most important role in the growth and development of soil faunal. Here we examined the seasonal distribution characteristics of the soil microarthropod communities in the Reaumuria soongorica shrubland of the Urat desert steppe in northwestern China in spring, summer, and autumn 2019 and their relationship with environmental factors. Our results showed that the total abundance and group richness of soil microarthropods community in summer was significantly greater than that in spring and autumn. There were two indicator taxon (Cryptopalmites and Isotomidae) in summer, one indicator taxon (Stigmaeidae) in autumn, whereas no indicator taxon in spring. The partial RDA results showed that soil moisture content and soil temperature were the main environmental factors that affected the distribution of soil microarthropods. From the results, we conclude that the abundance distribution of different dominant groups responds differently to seasonal changes. In addition, sensitivity and adaptability to environmental factors vary, especially soil temperature and soil moisture content.